Delayed diagnosis of foreign body aspiration in children. Issue 1 (1st January 2003) - Hilliard, T; Sim, R; Saunders, M; Hewer, S Langton; Henderson, J
Abstract : Foreign body aspiration in children is common and usually presents with an initial episode of choking with subsequent respiratory symptoms. There may be cough, wheeze, or stridor, with decreased or abnormal breath sounds on examination. However, it can mimic other illnesses and cause difficulty in diagnosis. Radiological investigations may help to confirm aspiration but should not be used to exclude it. Three cases are presented of foreign body aspiration with a delay in diagnosis ranging from days to weeks. It is believed that delay could have been avoided with a more careful approach to the history and more appropriate use of investigations. These cases demonstrate that children with a history of choking and subsequent symptoms should be referred for bronchoscopy.